Numerical simulation of rock-breaking under the impact load of self-excited oscillating pulsed waterjet. (February 2020) - Li, Hongsheng; Liu, Songyong; Jia, Jiguang; Wang, Fengchao; Guo, Chuwen
Abstract: To investigate the rock-breaking performance of the self-excited oscillating pulsed waterjet (SOPW), the finite element method (FEM) combined with smoothed particle hydrodynamics (SPH) was utilized to simulate the rock-breaking process. First, the rock-breaking status of a continuous waterjet and SOPW impact were compared and the rock-breaking mechanism including the formation and propagation of cracks and the formation of the crushing zone were observed. Under the same conditions, the rock-breaking performance of SOPW was found to be superior to that of the continuous waterjet. In addition, the failure of the crack propagation and crushing zone formation results in brittle failure and plastic behavior, respectively. The hammer pressure generated at the initial stage is the major factor for rock-breaking using a continuous waterjet. In the case of the SOPW, the hammer pressure can be generated at a high frequency, which indicates that SOPW can more effectively exploit energy and hammer pressure than a continuous waterjet. In addition, the rock-breaking performance with different pulse amplitudes, pulse frequencies, and confining pressures was discussed. The results indicate that the greater the pulse amplitude, the more severe the rock damage. However, a regular trend was not observed for rock-breaking performance with increase in pulse frequency. In addition, with increase in confining pressure, the rock-breaking performance initially decreased and then increased and the main conical cracks gradually became vertical to the side surface.